2013
DOI: 10.1182/blood-2013-05-468694
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in tissue repair: control of apoptosis and interactions with regenerative cells

Abstract: Besides mediating primary hemostasis and thrombosis, platelets play a critical role in tissue repair and regeneration. They regulate fundamental mechanisms involved in the healing process including cellular migration, proliferation, and angiogenesis. Control of apoptosis/cell survival and interaction with progenitor cells, which are clinically relevant but poorly understood aspects of platelets in tissue repair, will be highlighted in this review. Gaining deeper insight into the less well-characterized molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(135 citation statements)
references
References 70 publications
1
133
0
1
Order By: Relevance
“…VEGF) are critical regulators of angiogenesis prompting both angiogenic and angiostatic responses under diverse pathophysiological circumstances [11]. CXCL14 has been previously described to exert angiostatic properties [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF) are critical regulators of angiogenesis prompting both angiogenic and angiostatic responses under diverse pathophysiological circumstances [11]. CXCL14 has been previously described to exert angiostatic properties [20].…”
Section: Resultsmentioning
confidence: 99%
“…Platelets are a major source of chemokines and are able to release substantial amounts of chemokines rapidly within minutes into the microenvironment at the site of platelet accumulation. Thus, platelet-derived chemokines are powerful mediators of inflammation, immune defense, and repair mechanisms following vascular or tissue damage [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In the meantime, research has focused mainly on these 3 approaches: (1) developing AAV vectors with stealthier capsids that have reduced presentation of major histocompatibility complex class I; (2) limiting innate immune signals; and (3) improving FIX expression levels and specific activity, with the goal of obtaining therapeutic FIX expression while avoiding detection by the immune system. [4][5][6][7] By using a computational approach, Nair et al identified highly and lowly expressed genes in human liver tissue. After eliminating lowly expressed genes, they extracted the highly expressing gene promoter sequences and transcription factor binding sites from a database and processed the data through an analysis algorithm (panel A).…”
Section: Org Frommentioning
confidence: 99%
“…These findings led to the appreciation of the role of platelets in tissue remodeling, inflammation, angiogenesis, immunity, and antimicrobial host defense. [5][6][7][8][9] Bacteria have been shown to interact with platelets through their surface proteins, which are strainspecific. 10 It is largely believed that this interaction of platelets with bacteria is the initial step of host defense.…”
mentioning
confidence: 99%